A retrospective comparative study to evaluate the accuracy of ultrasound and multidetector abdominal computed tomography in the diagnosis of acute appendicitis - Abdel N Ghareep; Lamya A Bekhet; Ola I Saleh; Rashad Al-Fkey (Wolters Kluwer Medknow Publications, 2018)
Objectives The aim of this study was to compare the diagnostic accurateness of ultrasound (US) with that of multidetector computed tomography (MDCT) for the diagnosis of appendicitis in patients with doubted acute appendicitis (AA). Patients and methods A retrospective study was carried out on 110 patients of all age groups in the period between November 2014 and January 2016. All patients presented to the emergency department in our institute with suspected diagnosis of AA using sonography and MDCT. Results US diagnosed correctly AA in 70/75 (93.3%) cases confirmed on histopathology. Computed tomography diagnosed correctly AA in 74/75 (98.6%) cases that confirmed on operation and by histopathology. Conclusion MDCT has mild superiority to US in the diagnosis of AA; however, US with expert hands and newer US machines have high sensitivity and specificity in the diagnosis, and without the hazards of radiation.